СОСТОЯНИЕ ФОНДОВОГО РЫНКА КАЗАХСТАНА - Калдияров, Д А; Калдияров, С Д (Journal of Economic Research & Business Administration, 2015)
This article is concerned with stock market’s demands and its present condition.